The contestation of cultural claims in online media between Malaysia and Indonesia - Mulyana, Deddy; Yaputra, Albert (Faculty of Communications Science, Dr. Soetomo University, 2020)
The dynamics of Indonesia-Malaysia relations are influenced by the political growth of the two countries. Since the beginning of the Independence Era, there have been many ups and downs between the two countries. The recent ‘conflict’ centred on cultural issues, more specifically on the claims of certain cultural features such as songs, dances, batik, and cuisine. This study explained the reality of online media development in both countries, especially those related to Indonesian culture in Malaysia. This research used qualitative methods with a case study approach. Data were collected through interview, observation, and study of literature techniques. The results revealed that the construction of reality presented by the media was generally only seen from an Indonesian perspective, not much from a Malaysian perspective. Although the social reality of Malaysia’s ‘cultural claims’ did not reflect the thinking of all Indonesians, this conflict was actually driven more by a small group of Indonesians whose loyalty is unclear. Unlike the Indonesian media, Malaysian media did not consider art and culture originating from Indonesia as an important issue. So, the problem was not widely reported. Malaysian media believed that Indonesian media was exaggerating the fact and that it was only in the interest of the mass media to find exciting news to publish.